IgG reactivity to different desmoglein-3 ectodomains in pemphigus vulgaris: novel panels for assessing disease severity - Tavakolpour, Soheil; Noormohammadi, Zahra; Daneshpazhooh, Maryam; Gholami, Alireza; Mahmoudi, Hamidreza (Frontiers in Immunology, 2024)
Pemphigus vulgaris (PV) is an autoimmune disease characterized by IgG autoantibodies targeting desmoglein-3 (Dsg3), leading to blistering of mucous membranes and skin. Although commercial ELISA kits effectively diagnose PV, correlation with clinical phenotype remains unclear. This study assesses multiple panels for monitoring disease severity and activity by profiling IgG autoantibodies against Dsg3's various extracellular ectodomains. We designed and expressed different extracellular domains of Dsg3 in HEK293T cell line and developed 15 different ELISA panels, each using a single or multi ectodomains encompassing the entire extracellular region of Dsg3 to detect specific autoantibodies against the particular part of Dsg3. For evaluation of IgG autoantibody profiles in our panels, 59 PV patients were included, along with 11 bullous pemphigoid patients, and 49 healthy controls. For all the included subjects, 15 predefined ELISA panels were tested. The IgG autoantibodies against EC1 were detected in 86% of patients with a positive full Dsg3 ectodomain (EC1-5) ELISA, with 26% against EC2, 14% for EC3, 29% for EC4, and 23% for EC5. Among the panels with multiple Dsg3 ectodomains, EC1-3 and EC1-4 were representative of the entire Dsg3 ectodomain in terms of ELISA positivity across all included patients. A significant correlation (P<0.05) was observed between ELISA optical density (OD) and Pemphigus Disease Area Index (PDAI) scores in five panels, EC1, EC2-3, EC2-5, and EC3-4 in addition to the full ectodomain. It suggests an association with disease severity. Interestingly, while the ELISA panel for the entire Dsg3 extracellular ectodomains did not differentiate disease phases, three of our panels, including EC1, EC3-5, and EC2-5, ANOVA analysis showed a statistically significant difference between the groups of patients in remission, partial remission or persistent lesions, and those with active disease; EC1 was the only one that showed a significant difference in the multiple comparisons analysis; The level of autoantibodies against EC1 was not only correlated with the full ectodomain but also associated with higher disease severity and active disease phase. This study indicates that a detailed autoantibody profile against Dsg3 ectodomains could serve as a marker for PV severity and activity which may potentially enhance early treatment initiation.